1995
DOI: 10.1146/annurev.pc.46.100195.003115
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Structural Transformations in Semiconductor Nanocrystals

Abstract: Pressure-induced structural transformations in semiconductor nanocrystals are examined. High-pressure Raman spectroscopy, EXAFS, X-ray diffraction, and optical absorption are discussed as methods for studying these transformations in CdSe, CdS, and Si nanocrystals. In these nanocrystal systems, each technique shows an elevation in solid-solid structural transformation pressure as crystallite size decreases. By analogy with melting in nanocrystals, this elevation in transformation pressure is explained in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
247
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(264 citation statements)
references
References 0 publications
16
247
0
1
Order By: Relevance
“…The melting temperatures of metal clusters is size dependent (51). Pressure-induced structural transformations are more facile for smaller clusters and have lower activation energy (52).…”
Section: Studies Of Structural and Electronic Properties Of Metal Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…The melting temperatures of metal clusters is size dependent (51). Pressure-induced structural transformations are more facile for smaller clusters and have lower activation energy (52).…”
Section: Studies Of Structural and Electronic Properties Of Metal Nanmentioning
confidence: 99%
“…Pressure-induced structural transformations are more facile for smaller clusters and have lower activation energy (52). The nanocrystals are more perfect, because they cannot support dislocations because of their small size (51). The 2D phase diagram that is applicable to surface systems permits miscibility of metals to form solid solutions that are immiscible in 3 dimensions (53).…”
Section: Studies Of Structural and Electronic Properties Of Metal Nanmentioning
confidence: 99%
“…5 In addition, for some materials there is evidence that the bulk modulus and equation of state depend on crystallite size. 5,6 The Young's modulus of some nanocrystalline materials may be a function of particle size for reasons of porosity. 7 On the other hand, a Mössbauer spectrometry study on nanocrystalline iron ͑␣-Fe͒ has indicated that the grain boundary regions have a bulk modulus approximately 15% of that of the interior crystalline regions.…”
Section: Introductionmentioning
confidence: 99%
“…A cubic to trigonal structural distortion along a 3-fold rotational axis was discovered by careful and comprehensive analysis of the apparent lattice parameter and full width at half maximum, which are strongly dependent upon the Miller index and crystal size. 1 In the past fifteen years, much attention has been paid to the high pressure behavior of nanomaterials, especially the pressure-induced structural transformations in semiconductor 1O nanocrystals. I -In contrast, there are few reports on structural transformations and distortions in noble metals under high pressure due to their close-packed structures.…”
mentioning
confidence: 99%